Crisis on campus : confronting academic misconduct - Decoo, Wilfried, 1946- (Bradford book., 2002)
"This book presents an overview of the phenomenon and handling of academic misconduct. After introducing a brief historical background, it discusses contemporary circumstances that affect the nature and frequency of academic misconduct. It then details the phases of misconduct discovery and investigation: detection, analysis, assessment, reporting, and institutional handling. The final chapter deals with prevention. The book focuses on concrete cases, showing the complexities and ambiguities in dealing with presumed academic misconduct. The book also provides practical advice to both whistle-blowers and those accused of academic misconduct." "The book pays special attention to plagiarism, one of the most frequent but also most complex forms of academic misconduct. It analyzes the various degrees of possible plagiarism, detection techniques, challenges in proving plagiarism, and denial tactics. It also offers advice on how to report and handle cases of alleged plagiarism, both by students and by professionals."--Jacket